Exploration of the self-regulated learning process of Maya speaking university students - Chan-Martín, Elayne Dinora; León Islas, Eugenio Elías (IE Revista de Investigación Educativa de la REDIECH, 2017)
Self-regulation is a distinctive capacity of the human being. Its influence on the academic learning performance is decisive. Students who self-regulate their learning carefully observe their own behavior in relation to their goals and reflect on undergoing achievements, oriented towards transformative learning, not purely reproductive. This research makes an exploration of the self-regulated learning process in university students. The sample consisted of 40 students of Mayan origin, of which 57.5% is female and 42.5% male. The subjects of the research sample attended the 6th semester of university, enrolled in six different Educational Programs of the Intercultural Maya University of Quintana Roo. All of them were students who studied the Maya Language level IV. To measure the level of learning self-regulation, the Interactive Assessment of the Teaching-Learning Process (Escala de la Evaluacion Interactiva del Proceso de Enseñanza Aprendizaje, in short EIPE-6) was applied. The results indicate that in the process of self-regulation in the classroom when correlating the variables language and planning, the correlation is significant at the 0.01 level (r = -0.579) and in the self-regulation in general, the correlation is significant in the level 0.01 (r = -0.436). 40% of the students plan accordingly, 25% execute the planned, and 45% engage in self-reflection. Language does not influence the self-regulated learning process. Self-regulation is a determining variable for transformative learning.